HUBUNGAN TINGKAT PENGETAHUAN DENGAN SIKAP IBU TERHADAP PIJAT BAYI DI KELURAHAN SIDANEGARA WILAYAH KERJA PUSKESMAS CILACAP TENGAH I TAHUN 2017 - TRI BUDIARTI; Sohimah Sohimah; Izza Musyarofah (Universitas Harapan Bangsa Purwokerto, 2017)
Growth and development of a baby when at the age of 0-11 month or known golden period is depending on their parent. One of stimulation good growth and development of a baby with baby massage which a lot of benefits. Sidanegara is one of region in Cilacap, Central Java which has 397 of baby with baby massage to care the baby. So that baby massage have many benefit, their parent must have knowledge and attitude to baby massage. The purpose of this studi to know correlation knowledge with attitude of mother’s baby to baby massage in Sidanegara region in Central Cilacap I year 2017. This research is analytic survey with cross sectional desain, which sample is all mother’s baby in Sidanegara 2017 taken with cluster random sampling by 88 responden. The information knowledge and attitude taken with quisioner and the next analized with chi square. The result most of the knowledge is less to baby massage by 41 mother’s baby (46,6%) and most of attitude is support to baby massage by 82 mother’s baby (93,2%). Analized chi square knowledge and attitude with p-value is 0,461. There is no correlation knowledge with attitude of mother’s baby to baby massage. Keywords : Knowledge, Attitude, Mother’s Baby, Baby Massage.